2016
DOI: 10.4103/0976-237x.194108
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of salivary sialic acid in oral premalignancy and oral squamous cell carcinoma

Abstract: Aims:Oral cancer is the most life-threatening disease of oral tissues. In societies where the incidence of oral cancer is high, clinically recognizable premalignant lesions are particularly common. Diagnosing oral cancers at an early stage is critical in improving the survival rate and reducing the morbidity associated with the disease. Alterations in the sialic acid levels in cancer patients have stimulated interest in this sugar residue as a possible tumor marker.Settings and Design:The purpose of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
1
12
0
6
Order By: Relevance
“…6 Estimation of sialic acid in serum may act as an adjunct to conventional biopsy and salivary sialic acid estimation may provide a noninvasive and cost-effective method for screening the oral cancer patients. 16,17 In the present study, we observed that the mean rank of serum and salivary sialic acid levels (both protein bound and free) was three times higher among OSCC patients compared to the healthy controls. This signifies the fact that both serum and salivary sialic acid level can be used as an indicator of malignancy.…”
Section: Discussionsupporting
confidence: 52%
“…6 Estimation of sialic acid in serum may act as an adjunct to conventional biopsy and salivary sialic acid estimation may provide a noninvasive and cost-effective method for screening the oral cancer patients. 16,17 In the present study, we observed that the mean rank of serum and salivary sialic acid levels (both protein bound and free) was three times higher among OSCC patients compared to the healthy controls. This signifies the fact that both serum and salivary sialic acid level can be used as an indicator of malignancy.…”
Section: Discussionsupporting
confidence: 52%
“…Sialic acid is very important to determine the surface properties of cells and has been implicated in cellular invasiveness, adhesiveness and immunogenicity [ 46 ]. Previous studies in our laboratory demonstrated that malignant cells have been further sialic acid in their cell membrane than in normal cells and elevation of TSA in the plasma were found to reflect tumor burden, and correlated well with several stages of cancers including oral cancer [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the levels of sialic acid were reported to correlate very well with histopathological degree of the disease [69]. A similar study performed among control, oral premalignancy and oral squamous cell carcinoma (OSCC) patients (n = 30 each) also identified significantly higher levels of free sialic acid in OSCC and correlated with the grades of the disease in both OSCC and grades of dysplasia in premalignancy [68] indicating the role of free sialic acid as a screening and early detection marker for oral squamous cell carcinoma. Shetty et al, performed a cross‐sectional study to evaluate the levels of salivary malondialdehyde (MDA) involved in lipid oxidation among healthy subjects (HC), potential malignant disorders (PMD) and oral squamous cell carcinoma (OSCC) patients.…”
Section: Reviewmentioning
confidence: 96%
“…The ease in availability, sampling and especially the relevance in pursuing as a source of biomarkers in oral cancer [67–70], diabetes [71,72] and chronic oral inflammatory conditions such as periodontitis [72,73] makes saliva an important biofluid to study disease associated changes in lipid profile.…”
Section: Reviewmentioning
confidence: 99%